2011
DOI: 10.1111/j.1471-4159.2011.07467.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol causes the redistribution of L1 cell adhesion molecule in lipid rafts

Abstract: Fetal alcohol spectrum disorder is estimated to affect 1% of live births. The similarities between children with fetal alcohol syndrome and those with mutations in the gene encoding L1 cell adhesion molecule (L1) implicates L1 as a target of ethanol developmental neurotoxicity. Ethanol specifically inhibits the neurite outgrowth promoting function of L1 at pharmacologic concentrations. Emerging evidence shows that localized disruption of the lipid rafts reduces L1-mediated neurite outgrowth. We hypothesize tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 37 publications
2
54
3
Order By: Relevance
“…We have shown the ethanol interferes with this trafficking both in vivo and in vitro , and disrupts L1 signaling (Fig. 2 – 8, (Yeaney et al, 2009; Littner et al, 2013; Tang et al, 2006; Tang et al, 2011; Tang et al, 2011)). Recent evidence from several laboratories supports the important role of lipid rafts in ethanol toxicity (Sebastian and Nagy, 2005; Szabo et al, 2007; Blanco et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…We have shown the ethanol interferes with this trafficking both in vivo and in vitro , and disrupts L1 signaling (Fig. 2 – 8, (Yeaney et al, 2009; Littner et al, 2013; Tang et al, 2006; Tang et al, 2011; Tang et al, 2011)). Recent evidence from several laboratories supports the important role of lipid rafts in ethanol toxicity (Sebastian and Nagy, 2005; Szabo et al, 2007; Blanco et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…We have previously shown that ethanol alters the distribution of L1 in lipid rafts both in vitro (Tang et al, 2011) and in vivo (Littner et al, 2013). As shown in Figure 7, choline addition alone did not alter L1 distribution in lipid rafts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations